PENGGUNAAN MEDIA GAMBAR BERBASIS KEPEDULIAN LINGKUNGAN SEBAGAI PENGEMBANGAN BAHAN AJAR TEKS DESKRIPSI DENGAN MENGGUNAKAN METODE THINK TALK WRITE UNTUK TINGKAT SMP DI KOTA SEMARANG - Muhammad Asyhar Afif; Asropah .; Suwandi . (Teks: Jurnal Penelitian Bahasa, Sastra, dan Pengajarannya, 2021)
ABSTRACTThis research was conducted using the Research and Development (R&D) method adopted from Sugiyono which includes the following steps: 1) Preliminary Study, namely literature study and field study, 2). Development Studies, including: (1) initial product design, (2) design corrections from experts, (3) design revisions, (4) limited trials, (5) Focus Group Discussions (FGD), and (6) product revisions .The results of the expert / expert validation assessment show that the overall percentage obtained is 84.4% or if converted into criteria or categories gets the predicate worthy of being tested. After being validated, the learning media was tried out in the school under study and got the grade IV teacher's assessment in the two schools, the results were that the feasibility of presenting learning media for teachers got a score of 94%, while the results of student responses got a score of 95.7%, if converted into criteria or the category gets the predicate worthy.From the data above, it can be concluded that the developed teaching materials are categorized as suitable for use in learning activities. Use of Image Media Based on Environmental Concern for the Development of Teaching Materials Text Description Using the Think Talk Write Method can provide a fun new atmosphere for students so that students are motivated to participate in learning activities. Keywoards: Teaching Materials, Media, Pictures, Environmental Concern, TTW